2022
DOI: 10.3389/fpsyg.2022.975714
|View full text |Cite
|
Sign up to set email alerts
|

Automatic change detection: Mismatch negativity and the now-classic Rensink, O’Reagan, and Clark (1997) stimuli

Abstract: Change blindness experiments had demonstrated that detection of significant changes in natural images is extremely difficult when brief blank fields are placed between alternating displays of an original and a modified scene. On the other hand, research on the visual mismatch negativity (vMMN) component of the event-related potentials (ERPs) identified sensitivity to events (deviants) different from the regularity of stimulus sequences (standards), even if the deviant and standard events are non-attended. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 32 , 40 , 41 ) stimulus, in a stream of identical ones, can affect subjective duration judgments and lead to duration overestimations of the odd stimulation. Given that, to our knowledge, no studies on timing had tested whether more complex stimuli (i.e., natural scenes) could induce similar effects in an oddball setting (see also 42 44 for the use of more complex stimuli in variations of the oddball paradigm yet not in terms of time perception), we reasoned that our findings could further expand the literature around the oddball effect, as well as provide evidence on the role of attention on intervals’ duration estimates.…”
Section: Resultsmentioning
confidence: 99%
“… 32 , 40 , 41 ) stimulus, in a stream of identical ones, can affect subjective duration judgments and lead to duration overestimations of the odd stimulation. Given that, to our knowledge, no studies on timing had tested whether more complex stimuli (i.e., natural scenes) could induce similar effects in an oddball setting (see also 42 44 for the use of more complex stimuli in variations of the oddball paradigm yet not in terms of time perception), we reasoned that our findings could further expand the literature around the oddball effect, as well as provide evidence on the role of attention on intervals’ duration estimates.…”
Section: Resultsmentioning
confidence: 99%
“…If not, it would be unlikely that our foraging ancestor would have been able to detect those changes in visual properties, such as when a predator was approaching. A recent study by File et al [69] found that change-blindness does not imply the absence of visual representations or deficits in distinguishing regular and irregular visual representations [69]. Their findings indicate that even for the most subtle perceptual changes, our brain's encode such disparities.…”
Section: Smout Et Al [66] and Male And O'sheamentioning
confidence: 96%
“…The question is, what neural signatures reveal detection? File et al [69] reported posterior negativities �250 ms for undetected changes in scenery stimuli. This does not appear here.…”
Section: Smout Et Al [66] and Male And O'sheamentioning
confidence: 97%